Production of lactic acid and microbial biomass on distillery stillage by using immobilized bacteria - Mojović Ljiljana; Đukić-Vuković Aleksandra; Nikolić Svetlana; Pejin Jelena; Kocić-Tanackov Sunčica (Journal on Processing and Energy in Agriculture, 2014)
Lactic acid is versatile chemical with a wide range of applications in chemical, food, pharmaceutical, cosmetic and polymer industries. Currently, lactic acid world consumption is continually increasing mostly due to expansion of the application range of polylactides. Utilization of industrial distillery stillage, waste water from bioethanol production as a cheap and abundant substrate for integrated lactic acid and biomass production for animal feed could be a sustainable and environmentally friendly approach. In this study, integrated lactic acid and biomass production by fermentation with immobilized lactic acid bacteria Lactobacillus rhamnosus ATCC 7469 on an industrial waste stillage obtained from the Serbian bioethanol production plant 'Reahem' was studied. The immobilization was performed onto zeolite, a microporous aluminosilicate mineral. Optimal conditions for bacterial immobilization where determined which allowed easy cell separation from the fermentation media and their reuse in repeated batch cycles. A number of viable cells of over 1010 CFU g-1 of zeolite was achieved at the end of the fourth fermentation cycle. A maximal process productivity of 1.69 g L-1, maximal lactic acid concentration of 42.19 g L-1 and an average yield coefficient of 0.96 g g-1 were achieved in repeated batch fermentation with immobilized cells on the liquid stillage without mineral or nitrogen supplementation.